Handbook of Performability Engineering - Misra, Krishna B. (Springer London : Imprint: Springer, 2008)
Performability engineering provides us with the framework to consider both dependability and sustainability for the optimal design of products, systems or services. Whereas dependability is an aggregate of one or more of the attributes of survivability (such as quality, reliability, and maintainability etc.) and safety, and the present designs based on dependability and life cycle costs cannot be really called truly optimal since these attributes are strongly influenced by the design, raw materials, fabrication, techniques and manufacturing processes employed, and their control and usage. Therefore, sustainability, characterized by dematerilization, energy and waste minimization, disposability, reuse and recycling and other the environmental considerations which help in clean production, must be considered along with dependability. Design of 21st Century products, systems and services must conform to performability designs. More so when world resources are on the decline and to keep pace with rising population, the increased volume of production is bound to affect the world's environmental health further. As of now, dependability and cost effectiveness are primarily seen as instruments for conducting the international trade in the free market environment and thereby deciding the economic prosperity of a nation. However, the internalization of the hidden costs of environment preservation will have to be accounted for, sooner or later, in order to be able to produce sustainable products and systems in the long run. These factors cannot be ignored any more and must not be considered in isolation of each other. The Handbook of Performability Engineering considers all aspects of performability engineering, providing a holistic view of the entire life cycle of activities of the product, along with the associated cost of environmental preservation at each stage, while maximizing the performance.